ALTERNATIVES OF PROVIDING IPTV USING IP MULTIMEDIA SUBSYSTEM (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper, we specify the realization of IPTV platform based on IMS. We provide an analysis of advantages and disadvantages of possible alternatives of providing IPTV over IMS. On the example, which is contained in the case study are on the hypothetical area shown differences between given alternatives.